The Gene Signature of Activated M-CSF-Primed Human Monocyte-Derived Macrophages Is IL-10-Dependent - Cuevas, Víctor D.; Orta Zavalza, Emmanuel; Simón-Fuentes, Miriam; Samaniego, Rafael; Sánchez-Mateos, Paloma; Escribese, María; Cimas, Francisco J.; Bustos, Matilde; Pérez-Diego, Mario; Ocaña, Alberto; Domínguez-Soto, Ángeles; Vega, Miguel Á.; et al. (2021)
During inflammatory responses, monocytes are recruited into inflamed tissues, where they become monocyte-derived macrophages and acquire pro-inflammatory and tissue-damaging effects in response to the surrounding environment. In fact, monocyte-derived macrophage subsets are major pathogenic cells in inflammatory pathologies. Strikingly, the transcriptome of pathogenic monocyte-derived macrophage subsets resembles the gene profile of macrophage colony-stimulating factor (M-CSF)-primed monocyte-derived human macrophages (M-MØ). As M-MØ display a characteristic cytokine profile after activation (IL10high TNFlow IL23low IL6low), we sought to determine the transcriptional signature of M-MØ upon exposure to pathogenic stimuli. Activation of M-MØ led to the acquisition of a distinctive transcriptional profile characterized by the induction of a group of genes (Gene set 1) highly expressed by pathogenic monocyte-derived macrophages in COVID-19 and whose presence in tumor-associated macrophages (TAM) correlates with the expression of macrophage-specific markers (CD163, SPI1) and IL10. Indeed, Gene set 1 expression was primarily dependent on ERK/p38 and STAT3 activation, and transcriptional analysis and neutralization experiments revealed that IL-10 is not only required for the expression of a subset of genes within Gene set 1 but also significantly contributes to the idiosyncratic gene signature of activated M-MØ. Our results indicate that activation of M-CSF-dependent monocyte-derived macrophages induces a distinctive gene expression profile, which is partially dependent on IL-10, and identifies a gene set potentially helpful for macrophage-centered therapeutic strategies.